FT-IR, FT-Raman, Homo-Lumo and UV-Visible Spectral Analysis of E-(N′-(1H-INDOL-3YL) Methylene Isonicotinohydrazide) - D.Sumathi,; H., Saleem; A., Nathiya; N.RameshBabu,; D.Usha, (Journal of New Developments in Chemistry, 2017)
A combined experimental and theoretical study on molecular and vibrational structure of E-N¢ (ICINH) had been carried out. The FTIR, FT-Raman and UV-Vis spectra of ICINH were recorded in the solid phase. The optimized geometry was calculated by B3LYP method with 6-311++G(d,p) level of basis set. The harmonic vibrational frequencies, IR intensities and Raman scattering activities of the title compound were calculated at same level of theory. The scaled theoretical wavenumber showed very good agreement with the experimental values. The mulliken charges and thermodynamic functions of the ICINH were also performed at same level of theory. NLO and a study on the electronic properties such as excitation energies and wavelength, were performed by TD-DFT approach. HOMO–LUMO energy gap was also calculated and interpreted.